2019
DOI: 10.3144/expresspolymlett.2019.39
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ionic liquids on kinetic parameters of dicyanate ester polycyclotrimerization and on thermal and viscoelastic properties of resulting cyanate ester resins

Abstract: Cyanate ester resins (CERs) represent a family of thermosetting polymers possessing attractive intrinsic features, such as excellent dimensional stability, high glass transition temperature (T g > 250°С), low dielectric constants (2.5-3.2), flame-retardancy, and high adhesion to conductor metals and composites. Therefore, they are promising materials for aerospace and microelectronic applications, especially as polymer matrices for structural composites, adhesives, potting resins, and coatings that work under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 32 publications
(45 reference statements)
1
9
1
Order By: Relevance
“…It is also known that water can accelerate the cure of cyanate ester . Indeed, as shown in the results in Figure , we find that addition of 1% water along with 8% aliphatic IL resulted in an acceleration by a factor of 2.5 over the neat resin, which is very similar to Fainleib's more recent work . Although considerable care was taken in this work to ensure that the ILs did not absorb adventitious moisture, the water content of our ILs after storage for several months over dessicant is 0.2–0.3% based on Karl‐Fisher titration.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…It is also known that water can accelerate the cure of cyanate ester . Indeed, as shown in the results in Figure , we find that addition of 1% water along with 8% aliphatic IL resulted in an acceleration by a factor of 2.5 over the neat resin, which is very similar to Fainleib's more recent work . Although considerable care was taken in this work to ensure that the ILs did not absorb adventitious moisture, the water content of our ILs after storage for several months over dessicant is 0.2–0.3% based on Karl‐Fisher titration.…”
Section: Discussionsupporting
confidence: 85%
“…As mentioned, the acceleration of the cyanate ester reaction on addition of the aromatic [BnzC 1 im][NTf 2 ] IL that is observed in the present work depends on temperature and is smaller than the acceleration reported by Fainleib and co‐workers for an aliphatic imidazolium IL, 1‐octyl‐3‐methylimidazolium tetrafluoroborate [C 8 C 1 im][BF 4 ] that increased the reaction rate at 150 °C of BEDCy by a factor of three or up to several orders of magnitude . We use a similarly structured cation aliphatic‐based IL but with a different anion, [C 9 C 1 im][NTf 2 ] to investigate the aromatic versus aliphatic nature of IL, and we found that the reaction rate was accelerated by a factor of approximately two, consistent with but slightly less than Fainleib's more recent work.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations